2016
DOI: 10.2474/trol.11.382
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Raman Tribometry for the Formation and Removal Behavior of FeS<sub>2</sub> Tribofilm in the Scuffing Process

Abstract: We developed in situ observation and Raman analysis techniques for frictional interfaces and investigated the formation and removal behavior of the tribofilms that formed from a sulfur-containing extreme pressure (EP) additive on carbon steel. We detected an iron disulfide (FeS 2) tribofilm peak during the friction test and simultaneously detected D and G bands attributed to graphite-like products. Once scuffing occurred, both the FeS 2 peak and D and G bands disappeared. Therefore, the formation and removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…It is widely accepted that the distribution of asperity heights are very critical to scu ng [19] and to eliminate variations in roughness prior to the main test sequence, previous studies have suggested an initial running-in stage at very low sliding and entrainment speed and low load [15][16][17]. In the current study, the same 600 s running-in stage as developed by Peng [14] was employed, with a very low entrainment speed of 3 mm/s and a sliding speed of 0.01 m/s. These conditions are designed to give negligible EHD lm thickness to ensure a lot of asperity contact, but with little sliding to limit adhesive damage.…”
Section: Running-in Stagementioning
confidence: 83%
See 1 more Smart Citation
“…It is widely accepted that the distribution of asperity heights are very critical to scu ng [19] and to eliminate variations in roughness prior to the main test sequence, previous studies have suggested an initial running-in stage at very low sliding and entrainment speed and low load [15][16][17]. In the current study, the same 600 s running-in stage as developed by Peng [14] was employed, with a very low entrainment speed of 3 mm/s and a sliding speed of 0.01 m/s. These conditions are designed to give negligible EHD lm thickness to ensure a lot of asperity contact, but with little sliding to limit adhesive damage.…”
Section: Running-in Stagementioning
confidence: 83%
“…Palacios [13] applied EDX after a four-ball test to show that ZDDP tribo lm thickness increased as load increased, before becoming progressively thinner to eventually give scu ng at very high load. Miyajima et al [14] studied the role of EP additive in controlling scu ng alongside in situ observation of tribo lm development using a Raman tribometer. The authors used a starved contact to induce scu ng and showed that FeS 2 tribo lm formed initially, and this then thinned as rubbing progressed, to eventually give scu ng.…”
Section: General Introductionmentioning
confidence: 99%
“…In situ measurements of a surface in a contact area using Raman spectroscopy have primarily focused on the measurement of the chemical state (e.g., diamond-like carbon [24,25], tribofilms [31], and iron oxide [33]). The chemical state and surface temperature in the contact area can potentially be measured simultaneously using the method developed in the current study.…”
Section: Potential For Simultaneous Measurement Of Chemical State Andmentioning
confidence: 99%
“…In tribology, Raman spectroscopy can be used to investigate the chemical structures on a sliding surface [23][24][25][26][27][28][29][30][31][32][33]. In situ measurements of the sliding surface using Raman spectroscopy have been widely used during the last two decades [23,24,[26][27][28][29][31][32][33]. Almost all experiments were intended to detect dynamic changes in the chemical structure on the sliding surface.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress in understanding the structural evolution during friction was achieved due to the application of various in situ methods, which allowed evaluating structural changes occurring directly in the friction zone. In recent decades, new highly sensitive in-situ tribometers have been developed providing a high-frequency estimation of the friction coefficient and images of the contact zone [28][29][30], and, in some cases, information on chemical bonds using Raman spectroscopy [31,32]. Transparent pins and infrared cameras provide information about the temperature of the contact zone directly in the process of friction [33,34].…”
Section: Introductionmentioning
confidence: 99%